Immobilization of enzyme in Metal Organic Frameworks (MOFs) for enhanced activity, stability, and reusability - Sood, Tanu Priya (My University, 2024)
For a long time, enzymes have been exploited as catalysts for diverse processes. Despite the numerous advantages of biocatalysis, the utilization of enzymes for catalyzing processes necessitates certain environmental conditions that are sometimes incompatible with the structure and function of enzymes. Nevertheless, these challenges might be surmounted via enzyme immobilization onto solid substrates. Immobilization can enhance the stability, biocatalytic activity, and repeated usability of enzymes, leading to improved performance and increased commercial feasibility. Metal organic Frameworks (MOFs) have emerged as efficient substrates for immobilizing enzymes, attributed to their high surface area, porosity, stability, biocompatibility, and capability of providing micro-protective environment for enzymes. In this work, Zeolitic imidazolate framework-8 (ZIF-8) MOF was employed for insitu immobilization of commercially viable horse radish peroxidase (HRP) enzyme considering the low-cost and ambient synthesis of selected MOF. For this, ZIF-8 and HRP@ZIF-8 were synthesized under ambient conditions using co-precipitation method followed by extensive characterization. UV-Visible and Fourier transform infrared (FTIR) spectroscopy, BrunauerEmmet-Teller (BET) surface area analysis, along with SEM imaging were used for structural and functional characterization of synthesized ZIF-8 and HRP@ZIF-8. The presence of UV absorption peak around 280 nm related to proteinaceous enzyme and amide bond stretching at 1643 cm-1 in FTIR spectra of HRP@ZIF-8 indicated towards the successful immobilization of enzyme onto MOF. The X-ray diffraction (XRD) studies revealed that crystalline structure of ZIF-8 remained intact even after the enzyme immobilization with some bulges observed on the structure of HRP@ZIF-8 in scanning electron microscopy (SEM) imaging as compared to ZIF8. Next, the enzymatic activity, stability, and reusability of HRP after immobilization onto ZIF8 were assessed. The encapsulation of the enzyme within the MOF resulted in a notable enhancement of both its activity and stability. The immobilized HRP demonstrated a 46.53% increase in catalytic activity as compared to the free form and enhanced reusability, with 81% intact residual activity after five cycles. The explored biocatalytic platform also demonstrated improvement in operation stability and no significant leaching of enzyme from MOF. Therefore, enzyme-MOF based biocatalytic platforms have a wide scope & commercial applicability in various fields for industrial, biomedical, pharmaceutical and environmental processes.
Keywords: Enzyme; Immobilization substrates; Metal-organic frameworks; In-situ encapsulation